Determinants of technical efficiency among dairy farms in Chitwan, Nepal - Dhakal, S. C. (Journal of Agriculture and Forestry University, 2022)
Nepalese dairy sector has been showing structural changes with adoption of latest technologies like improved breeds, feeds, cultivated fodder and additives. In the context of these changes, this research was conducted to assess the technical efficiency and its determinants among dairy farms. The study was accomplished with primary data collected through face-to-face interview using semi-structured interview schedule from a sample of 240 dairy farms selected randomly using simple random sampling technique from 8 wards of Bharatpur Metropolitan City, Chitwan. Data were analyzed using descriptive statistics, stochastic production frontier and tobit regression model. Technical efficiency was found to be the highest in mix dairy farms (3.530) followed by cow farms (2.56) and buffalo farms (2.138). Labour was the most contributing factor in all three types of dairy farms. This study had shown that average annual income per farm should be Rs. 542000, Rs. 403225 and Rs. 611400 for getting 90% technical efficiency in milk production at buffalo, cow and mix farms, respectively. Similarly, 57% buffalo farms were operating at efficiency of 30-60%, 46% cow farms were operating at efficiency of 30%, and 67.5% mix farms were operating at efficiency of 30 to 60%. Total investment in dairy farming, training and adopting dairy as primary occupation were positively and significantly affecting technical efficiency on buffalo, cow and mix type of dairy farming system. There is still large scope to increase the annual milk production in the dairy farms of Chitwan through efficient use of available resources with the existing technologies. This is concluded that dairy farming system can be promoted efficiently by increasing total investment in dairy farming through easy access to loan, training on dairy animal production and management, ensuring dairy business as profitable primary occupation, promotion of fodder and pasture production, and securing easy access to medicines and additives.